Wayfinding and Evacuation in Stadiums: A Systematic Review of Spatial, Perceptual, and Crowd Management Factors - Muhammad Tafakur (TAMA: Journal of Visual Arts, 2026)
Wayfinding plays a crucial role in ensuring safe evacuation in complex, high-density environments such as stadiums. However, existing research tends to examine spatial design, human perception, and crowd management as separate domains, resulting in fragmented understanding of evacuation performance. This study presents a structured literature review to synthesize key factors influencing wayfinding in emergency contexts. The review identifies three major dimensions: (1) spatial and technical factors, including legibility, visibility, and signage systems; (2) human perceptual and psychological factors, such as decision-making under stress and behavioral responses; and (3) organizational factors, including crowd management and evacuation planning. The findings reveal that evacuation inefficiencies often arise from the lack of integration among these dimensions. This paper proposes a conceptual synthesis positioning wayfinding as a socio-spatial system, offering a more holistic framework for future research and design practice in stadium safety. Keywords: Wayfinding; Emergency Evacuation; Spatial Cognition; Crowd Management (Font Times New Roman,10pt, italic)